Correlations for nusselt number in a staggered cross-flow tube-type heat exchanger (2009)
Empirical correlations for Nusselt number (Nu) in a staggered multi-row multi-column cross-flow rube-type heat exchanger is presented in this paper. In the experiment, air at ambient temperature was drawn by a centrifugal fan perpendicularly over banks of cylindrical rods arranged in staggered configuration of 5 rows by 4 columns. A test element consisting of a tube of copper with length, internal and external diameters of 0.125, 0.0115 and 0.0125 m was heated to a maximum temperature of about 90°C and inserted into the air stream in the working section. Rate of cooling was measured by thermocouple embedded at the centre, via a digital multimeter which was connected to a computer for monitoring temperature data. A semi-logarithms plot of the data was used to calculate the heat transfer coefficient (h) between the copper element and air, and hence the Nusselt number. The heat transfer coefficient at the centre of each of the four columns at ten different flow rates with throttle valve openings ranging from 10 - 100% were investigated. Results showed that the Nusselt number increased exponentially with increase in air flow rate and also increased in successive columns in the direction of flow at a diminishing rate. Correlations of Nusselt number with Reynolds number (Re) were developed for preliminary design and performance assessment of staggered multi-row multi-column cross-flow tube-type heat exchanger.